Implementasi Pendidikan Karakter Religius Anak Usia Dini Oleh Orang Tua Berprofesi Petani di Jorong Lurah Dalam - Rima Handayani; Afrinaldi Afrinaldi; Januar Januar; Iswantir Iswantir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The focus of the research is used so that there are no mistakes in the discussion that the author will carry out, so the author limits it to the following problem: Implementation of religious character education for early childhood by parents who work as farmers in Jorong Lurah in Palupuh sub-district. This research is a type of qualitative research with a descriptive approach. Implemented in Jorong Lurah Dalam Agam Regency in August 2023 until completion. The research subjects were parents and children. Informants are parents, supporting informants are young children. Data collection uses interviews, observation and documentation. Validity techniques use source triangulation and engineering triangulation. Based on the research results, it was concluded that parents in implementing character education through the methods of example, habituation, advice and storytelling are very effective in their application because parents are always an example for their children. The obstacle that parents face in forming their children's character is the presence of external environmental factors that influence them, both positive and negative. Then, the availability of time that parents give to educate children's character at home is limited because parents are busy with work.